Comparing Hybrid and Flipped Modalities in Remote and Face-to-Face Learning in a Japanese University L2 Academic Writing Course - Lege, Ranson Paul (Journal of NELTA, 2023)
Teachers throughout the world are interested in the eff ectiveness of online and fl ipped class methods of instruction. During the Covid-19 pandemic, these platforms went from cutting edge to becoming the central teaching platform. Online classes in particular can be effective in teaching reading and writing. In 2013, a hybrid online class was introduced into the academic writing program at the Graduate School of Law at Nagoya University as a way to assist Master’s students with their writing needs. Between 2012 ‒ 2023, the same writing courses underwent three phases of development: hybrid, flipped, and fully remote. As part of an action research study, the process included stages of planning, implementing, observing, and refl ecting on the design of each of the learning platforms. For the planning and implementing phases, the paper compares the quality measures of the instructional designs. Surveys on student perspectives were used to help with the observing and reflecting phases. Student survey results indicated that, even during the peak of the pandemic, learners were satisfi ed with all three platforms as they developed.